The challenges of Holocaust instruction and remembrance - Particular and universal aspects in formal and informal interdisciplinary curricula in Israel and abroad - Davidovich, Nitza; Soen, Dan; Hezkelovich, Anat (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
The present article examines Holocaust instruction in Israel and in France, addressing formal and informal aspects of teaching practices. Specifically, the article examines whether Holocaust instruction constitutes a unifying factor that stresses what is common to human beings, among adolescents at schools in Israel and abroad, or whether it is a continuation of the methodic axis of the general model of the school and its credo. The study was conducted as part of a large-scale project evaluating 20 years of journeys to Poland by Israeli youth. It is based on a qualitative research apporoach that included analysis of interviews with policymakers, representatives of Holocaust institutes and foundations, teachers, students and guides. It also made use of field observations and official documents. The qualitative analysis revealed that that the dominant didactic models in Israel and France differ from one another in the importance that they attribute to universal versus the particular elements. Each of the models was built based on a didactic foundation of educational and teaching activity at the school in general, and Holocaust instruction in particular. The study findings indicate that in general, the Holocaust instruction in Israel continues to emphasize the particular. It serves as a tool for strengthening the unique values of the event, and stresses Israeliness, Zionism, and Jewishness. The climax of the modal is an eight-day journey to Poland, centering on a visit to Auschwitz. In contrast, Holocaust instruction in France emphasizes the universal. The curriculum positions the journey as the climax of the scholastic experience but, unlike the Israeli curriculum, it emphasizes the historical and universal aspects of the Holocaust and represses the singularity of the event in the context of the Jewish people. A comparison of the two countries underlines the substantive differences separating the two different educational systems, which have adopted different sets of values.